2012
DOI: 10.1249/mss.0b013e318249d701
|View full text |Cite
|
Sign up to set email alerts
|

Knee Extensor Fatigue Threshold Is Related to Whole-Body V˙O2max

Abstract: Performing submaximal bouts of knee extensor contractions, while monitoring EMG and deoxygenation, seems a feasible manner to estimate an aerobic capacity-related exercise intensity of peripheral fatigue onset. This test may be used to evaluate changes in endurance capacity of single muscle groups, without the necessity for all-out testing, which could be problematic with frail subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Additionally, it has been shown in the knee extensors that myoelectric manifestations of fatigue are only seen when the exertion exceeds 40% of the MVC (de Ruiter et al. ). Two exercises in a study by Plamondon et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been shown in the knee extensors that myoelectric manifestations of fatigue are only seen when the exertion exceeds 40% of the MVC (de Ruiter et al. ). Two exercises in a study by Plamondon et al.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained partly by recent studies which have demonstrated that frequency variables, including MNF, do not accurately predict motor unit recruitment during contractions (Merletti & Farina, 2016;Vecchio et al 2017). Additionally, it has been shown in the knee extensors that myoelectric manifestations of fatigue are only seen when the exertion exceeds 40% of the MVC (de Ruiter et al 2012). Two exercises in a study by Plamondon et al (2002) were similar in position and function to the Ito test; in that study, these exercises were found to be between 26 and 32% of a participant's MVC.…”
Section: Endurance and Fatiguementioning
confidence: 97%
“…One may reduce effects of ATT on the amplitude of [HHbMb] and [O 2 HbMb] signals by normalizing oxygenation changes to the oxygenation at peak exercise [ 10 , 27 ], maximal voluntary contraction [ 26 , 28 ] or cuff occlusion [ 21 , 26 ]. Still, this correction does not account for the evident asymmetry in Δ[O 2 HbMb] and Δ[HHbMb] amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is well-known that scattering and absorbance due to adipose tissue affect NIRS signals, reducing absorbance by underlying muscle tissue [ 24 – 26 ]. One may reduce these effects of ATT by normalizing oxygenation changes to the oxygenation at peak exercise [ 10 , 27 ], maximal voluntary contraction [ 26 , 28 ] or cuff occlusion [ 21 , 26 ], where the effect of ATT on the amplitude of separate [O 2 HbMb] and [HHbMb] signals can be assessed in the absence of blood volume changes.…”
Section: Introductionmentioning
confidence: 99%
“…Before beginning the exercise, the subjects performed a few repetitions of light intensity to warm-up. The exercise protocol consisted of 4 sets of seated knee extensions (30,15,15, and 15 reps), separated by 1-minute periods, with BFR applied throughout the sets and rests. It was based on the recommendations of previous studies examining the implementation into clinical practice of LL-BFR resistance training, its considerations of methodology, safety, and physiological responses (20,36,45), albeit we opted for 60 seconds rests instead of 30 seconds to minimize fatigue, discomfort, and to avoid possible adverse effects, as concerns have been raised regarding the potential risk for muscle damage and rhabdomyolysis with very strenuous and unaccustomed BFR exercise under some circumstances (45).…”
Section: Methodsmentioning
confidence: 99%